Academic performance and satisfaction levels in high school students - Arias Cano , María Emilia (2025)
The relationship between academic performance and student satisfaction is a topic of growing interest in the educational field, since both factors are fundamental for the academic and personal success of students. The objective of this article is to analyze the relationship between academic performance and levels of satisfaction among third-year high school students at the Salesian Educational Unit, in Ecuador. It was developed under the positivist paradigm, the quantitative approach and the type was analytical-correlational. The population that participated in this process was 35 students aged between 17-18 years. A survey was applied, validated by Cron Bach's Alpha, whose assessment generates a reliability level of 0.89. The results were the affirmation of the relationship between Academic Performance and Student Satisfaction. Concluding that, there are important implications for the design and implementation of effective educational policies